Muriel's wedding [videorecording (DVD)] - Collette, Toni; Hunter, Bill, 1940-2011; Griffiths, Rachel, 1968- (Miramax classics., 1999)
No one ever paid much attention to Muriel and her humdrum small town life, so she and her best friend Rhonda decide to leave it behind and head for the big city ... where they end up having the exciting adventure of their lives! What's more, soon everyone takes notice when Muriel becomes engaged to a handsome and popular sports hero!